Proceedings of the International Scientific Conference (Моделювання, керування та інформаційні технології, 2015)
Proceedings of the International Scientific Conference «Modern Problems of Mathematical Modeling and Computational Methods». – Rivne :EPD RSHU, 2015. – 229 p.